2020
DOI: 10.1088/1361-6471/ab920c
|View full text |Cite
|
Sign up to set email alerts
|

Possible ‘stapler’ band in 109Ag nucleus

Abstract: High-spin states of 109Ag have been studied using the 7Li + 110Pd reaction at a beam energy of 46 MeV. A negative-parity band decaying to the ground-state band by several new linking transitions is established. Meanwhile, seven new E2 crossover transitions of this band are observed, thereby confirming the spin-parity assignment and ordering of the dipole transitions above the Iπ = 19/2− level. A low energy γ-ray transition of 88 keV is found and placed at the bottom of the negative-parity band, and thus the Iπ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Alternatively, it has been reported that shells of graphene oxide (GO) may be developed from the GO self‐assembly on oil/water interface within Pickering emulsions 21–23 . GO is known to be able to satisfy the demands for the shells of microcapsules, due to its special 2D material, which covers sp 2 and sp 3 ‐ hybridization carbon and considerable oxygen‐containing functional groups 24–27 . Due to the chemistry element and molecular configuration pertaining to GO, 28 GO nanosheets possess dispersibility, amphiphilicity, and flexibility in water and can adhere onto the interface in a spontaneous manner with reducing interfacial energy, which become a kind of 2D surfactant 29–32 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it has been reported that shells of graphene oxide (GO) may be developed from the GO self‐assembly on oil/water interface within Pickering emulsions 21–23 . GO is known to be able to satisfy the demands for the shells of microcapsules, due to its special 2D material, which covers sp 2 and sp 3 ‐ hybridization carbon and considerable oxygen‐containing functional groups 24–27 . Due to the chemistry element and molecular configuration pertaining to GO, 28 GO nanosheets possess dispersibility, amphiphilicity, and flexibility in water and can adhere onto the interface in a spontaneous manner with reducing interfacial energy, which become a kind of 2D surfactant 29–32 .…”
Section: Introductionmentioning
confidence: 99%